Social Studies Teachers' Views on the 7th Grade Social Studies Teacher Guidebook and its Removal: A Q Method Analysis - Cakmak, Zafer; Akgun, Ismail Hakan; Kacar, Turan (Turkish Education Assoc, 2022)
For the curriculum to be implemented more effectively and efficiently, the Ministry of National Education (MoNE) has distributed teacher guidebooks to primary and secondary school teachers since the 2005-2006 academic year. In 2018, the teacher guidebooks, which instruct and advise teachers in the delivery of the course, were abolished. However, the literature has a significant number of studies on the value of teacher guidebooks. Using Q methodology, the goal of this study is to determine the views and perceptions of social studies teachers working in Diyarbakir (a city located in eastern Turkey) regarding the Ministry of National Education's 7th grade social studies teacher's guidebook distributed until the 2018-2019 academic year and the removal of these books. The mixed-method research technique was used to conduct this study, which contains both qualitative and quantitative elements. In this phenomenological study, an online interview was conducted via Zoom using the Q methodology. The study group consisted of 30 social studies teachers from several secondary schools in Diyarbakir, each with a varied level of professional experience. The data were collected using the Q methodology form, which was produced by the researchers following the literature and the opinions of experts in the field. This form included the Q items, the Q sort in which these items were placed, and open-ended questions to determine the participants' views on extreme values. The PQMethod 2.35 software was used to examine the data in the Q sort in the Q methodology form filled out by the participants. The answers submitted by the participants to the open-ended questions were analyzed using descriptive analysis. According to the findings of all the analyses, it was determined that the 7th grade social studies teacher's guidebook had positive aspects and that removing these books had negative consequences for social studies teachers, and that it would be more beneficial to redevelop the guidebooks and present them to teachers for use. It is reasonable to conclude that the removal of the teacher will have for new teachers. Furthermore, it has been suggested that the future guidebook for social studies teachers should facilitate course activities, eliminate the lack of knowledge in the course content, and assure the efficiency of time management.
Keywords: Teacher guidebook; Q methodology; Social studies; Social studies teachers; 7th grade